System and method for motion capture - Madsen, N. H.; McLaughlin, T. M.; Wilmink, R. J. H.; Glover, R. M. (2008)
A method for capturing motion associated with a subject in real-time, comprising: defining a plurality of elements, wherein each element corresponds to at least one interconnected segment of the model; defining a plurality of marker positions, wherein each marker position is associated with an element; defining a predetermined condition; defining a value for a variable when the predetermined condition is satisfied, wherein a possible position of a first element is restricted by the value; for each of a plurality of frames, predicting locations for the markers, by: determining whether the predetermined condition is satisfied; and if the predetermined condition is satisfied, then associating the value with the variable so that the possible position of the first element is restricted; and measuring locations of the markers; and determining positions of the elements by comparing the predicted locations for the markers with the measured locations of the markers.